Analisis Kebutuhan LKPD Fisika Berbasis Discovery Learning untuk Meningkatkan Minat dan Hasil Belajar Siswa SMP - Isnain Janah; Ovilia Putri Utami Gumay (Journal on Education, 2025)
The aim of this research is to conduct a needs analysis to help teachers and students more easily visualize the learning process and help students understand the subject of vibrations, waves and sound. This research is a quantitative approach research. The research carried out was descriptive. The subject of this research is the physics teacher at Karya Sakti State Middle School. After conducting a needs analysis, it was concluded that there was a need for teaching materials that made it easier for students to understand the learning content. The teaching materials are student worksheet teaching materials based on Discovery Learning on vibrations, waves and sound.